2017
DOI: 10.1002/cbin.10731
|View full text |Cite
|
Sign up to set email alerts
|

Activated macrophages as key mediators of capsule formation on adipose constructs in tissue engineering chamber models

Abstract: In plastic and reconstructive field, it would be much beneficial to fabricate an engineered adipose tissue substitute allowing reliable and complete fat tissue regeneration. Tissue engineering chamber (TEC) holds the promise to optimize an adipogenic configuration that is efficacious as well as reproducible. A frequently occurring complication involves the adipose tissue flap encapsulation and, effectively, its shielding, by a thick fibrous membrane, which hinders development into the proliferative stage. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Notably, our findings showed that IL‐2 levels increased and peaked at 24 hr. Moreover, some studies have shown that macrophages secrete various proinflammation factors, such as IL‐6 and IL‐2 (Brown, Ratner, Goodman, Amar, & Badylak, ; Debels et al, ; Zhan & Lu, ). However, the number of macrophages peaked at 2 weeks, which was later than the peak time of IL‐2.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, our findings showed that IL‐2 levels increased and peaked at 24 hr. Moreover, some studies have shown that macrophages secrete various proinflammation factors, such as IL‐6 and IL‐2 (Brown, Ratner, Goodman, Amar, & Badylak, ; Debels et al, ; Zhan & Lu, ). However, the number of macrophages peaked at 2 weeks, which was later than the peak time of IL‐2.…”
Section: Discussionmentioning
confidence: 99%
“…9 Moreover, reviewing the literature, it has been found that these protein factors, such as VEGF and EGF, can promote neovascularization, while BDNF, HGF, PDGF, GDNF, and others can inhibit M1 polarization and promote the M2 polarization of macrophages. 23,[48][49][50][51][52][53][54][55][56] Additionally, M2 macrophages can promote angiogenesis in vivo. 57 In this study, we validated these factors using ELISA (Table 1) and believe that they be important reasons for promoting macrophage M2 polarization.…”
Section: Discussionmentioning
confidence: 99%
“…detected many important protein factors in CEFFE, including BDNF, GDNF, TGF‐β, HGF, bFGF, VEGF, PDGF, EGF, NT‐3, and G‐CSF 9 . Moreover, reviewing the literature, it has been found that these protein factors, such as VEGF and EGF, can promote neovascularization, while BDNF, HGF, PDGF, GDNF, and others can inhibit M1 polarization and promote the M2 polarization of macrophages 23,48–56 . Additionally, M2 macrophages can promote angiogenesis in vivo 57 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, Crdf induced transient M2-polarized macrophages infiltration, in contrast to the chronic M1 macrophages in the Df group. Previous studies had shown that rapid inflammatory responses could activate chemotaxis of host-derived mesenchymal stem cells and promote angiogenesis in the early stage of grafting ( Zhan and Lu, 2017 ; Cai et al, 2018 ). While persistent high levels of macrophage infiltration inhibit adipogenesis and cause severe fibrosis ( Cai et al, 2017a , b ).…”
Section: Discussionmentioning
confidence: 99%